Delongia flavolimbata (S.He & Y.J.Yi) S.He & Y.J.Yi, an unusual species with elamellate laminae from China, newly combined in Polytrichaceae based on molecular data. (2nd October 2021) - Yi, Yan-Jun; Zhang, Jie; Xiao, Xiao-Xuan; He, Si
ABSTRACT: Introduction: Hyophila flavolimbata S.He & Y.J.Yi has several unusual morphological features that cast doubt on its current generic position in Hyophila and even its family placement in the Pottiaceae. The results of a molecular study carried out to investigate the taxonomic identity of this taxon have provided a unique resolution. Methods: In addition to a morphological examination in which material from related species were compared, rps4 and trn L–F sequences from the type specimen and a newly identified specimen of Hyophila flavolimbata were analysed. Relationships between related species in the Polytrichaceae were explored using Maximum Likelihood and Bayesian inference analyses. Key results and conclusions: Phylogenetic analysis resolved a new taxonomic position for Hyophila flavolimbata in the genus Delongia of the Polytrichaceae, and consequently, a new combination, Delongia flavolimbata (S.He & Y.J.Yi) S.He & Y.J.Yi, is made. Photographs detailing key morphological differences from related taxa, and a key to the three currently recognised species in Delongia, are provided. The completely elamellate laminae of this species are an unusual morphological character that is highly remarkable for Delongia and uncommon in the Polytrichaceae.